CITIZENSHIP, RELIGION, AND RIGHTS: A Critical Assessment of Discrimination and Legal Inequality in Malaysia - Palawa, Alimuddin Hassan; Nuh, Zulkifli M (Asia-Pacific Journal on Religion and Society, 2024)
This article critically examines how law and policy in Malaysia operate not only as instruments of governance, but also as mechanisms of exclusion, particularly at the intersections of citizenship, religion, gender, and identity. Drawing on the landmark report Washing the Tigers (Equal Rights Trust & Tenaganita, 2012) and utilizing a rights-based, interdisciplinary framework, the study reveals how Malaysia’s dual legal system, ethno-religious nationalism, and moral governance produce a stratified regime of belonging and legal recognition. Through qualitative discourse analysis and a postcolonial theoretical lens, the article explores three key domains: (1) stratified citizenship and racialized statehood; (2) religious governance and the erosion of pluralism; and (3) gendered moral regulation and the criminalization of difference. The findings demonstrate that discrimination in Malaysia is not incidental but structural—codified into law and normalized through ideology. The study concludes by calling for a radical reconfiguration of the legal and normative foundations of citizenship in Malaysia, toward a plural, inclusive, and rights-based polity. This article contributes to broader discussions on legal pluralism, postcolonial statecraft, and the politics of difference in Southeast Asia.